Performance characteristics optimization of CRDI engine fuelled with a blend of sesame oil methyl ester and diesel fuel using response surface methodology approach - Kumar, Manish; Gautam, Raghvendra; Ansari, Naushad Ahmad (Frontiers in Mechanical Engineering, 2023)
The primary aim of this experiment was to use response surface methodology (RSM) to optimize engine operating parameters for optimal performance and emission characteristics of a common rail direct ignition (CRDI) diesel engine fuelled with sesame oil methyl ester (SOME)/diesel blends. The experiments were carried out on a water-cooled CRDI engine with a 4-stroke, single-cylinder connected to an eddy current dynamometer. As input variables, the SOME% (0-20%), fuel injection pressure (FIP) (500-600 bar), EGR rates (0-14%), and engine load (0-12kg) were used. The optimization method is utilized to maximize brake thermal efficiency (BTE) while minimizing BSFC, CO, HC, and NOx emissions. Experimental research data were used to create the RSM model through DoE (Design of experiments). The most relevant factors impacting the responses were identified using an ANOVA analysis. According to the optimization findings, the engine's optimum working parameters were found to be a 20% SOME ratio, 577.5 bar FIP, 5.26% EGR rates, and 5.12 kg engine load. Under these operating circumstances, the optimal responses were determined to be 18.92% BTE, 0.3705kg/kWh BSFC, 0.03190% vol. CO, 13ppm HC, and 447.5ppm NOx emission. At the same time, R2 values were 96.35%, 87.54%, 91.57%, 95.87%, and 93.73% for BTE, BSFC, CO, HC, and NOx respectively.